Ex Vivo Resection and Autotransplantation for Conventionally Unresectable Tumors – An 11-year Single Center Experience. Issue 5 (November 2020) - Kato, Tomoaki; Hwang, Regina; Liou, Peter; Weiner, Joshua; Griesemer, Adam; Samstein, Benjamin; Halazun, Karim; Mathur, Abhishek; Schwartz, Gary; Cherqui, Daniel; Emond, Jean
Abstract : Background and Aims: Ex vivo surgery may provide a chance at R0 resection for conventionally unresectable tumors. However, long-term outcomes have not been well documented. In this study, we analyze our 11-year outcomes to define its role. Study Design: We retrospectively analyzed 46 consecutive patients who underwent ex vivo surgery at our institution 2008–2019. Results: The types of tumors were: carcinoma (n = 20), sarcoma (n = 20) and benign to low grade tumor (n = 6). The type of ex vivo surgery was chosen based on tumor location and vascular involvement. The most commonly performed procedure was ex vivo hepatectomy (n = 18), followed by ex vivo resection and intestinal autotransplantation (n = 12), ex vivo Whipple procedure and liver autotransplantation (n = 8) and multivisceral ex vivo procedure (n = 7). Twenty-three patients (50%) are currently alive with median follow-up of 4.0-years (11 months–11.8 years). The overall survival was 70%/59%/52%, at 1-/3-/5-years, respectively. Patient survival for benign to low grade tumors, sarcoma, and carcinoma was 100%/100%/100%, 65%/60%/50%, and 65%/45%/40%, at 1-/3-/5-years, respectively. Ninety-one percent patients had R0 resection, and 57% had no recurrence to date with median follow-up of 3.1-years. Two patients (4.3%) died within 30 days due to sepsis and gastroduodenal artety (GDA) stump blowout. Two additional patients died between 30 and 90 days due to sepsis. Perioperative mortality in the last 23 consecutive cases was limited to 1 patient who died of sepsis between 30 and 90 days. Conclusions: For a selected group of patients with conventionally unresectable tumors, ex vivo surgery can offer effective surgical removal with a reasonably low perioperative mortality at experienced centers.